Fog Computing Realization for Big Data Analytics - Mehdipour, Farhad; Javadi, Bahman; Mahanti, Aniket; Ramirez‐Prado, Guillermo (Fog and Edge Computing, 2019)
This chapter provides background on big data analytics and describes how fog‐engine (FE) can be deployed in the traditional centralized data analytics platform and how it enhances existing system capabilities. The FE provides on‐premise data analytics as well as the capabilities for Internet‐of‐Things (IoT) devices to communicate with each other and with the cloud. The chapter provides an overview of a typical FE deployment. It explains the system prototype and the results of the evaluation of the proposed solution. Two case studies describing how the proposed idea works for different applications are described. A table shows the list of IoT solutions from five well‐known cloud providers. Data collection is one of the basic aspects of these solutions, which specify the communication protocols between the components of an IoT software platform. Researchers have proposed various applications of fog computing in diverse scenarios such as health monitoring, smart cities, and vehicular networks.